Pemanfaatan Tiga Jalur Pendidikan Dalam Pengembangan Mutu Pembelajaran Etika Dan Moral - Anak Agung Raka Asmariani (UHN IGB Sugriwa Denpasar, 2018)
Each; Every birth that happened is appearance a new stupidity. This matter will experience of a transform through process instruction of science. Education band play a part very important.One of the important problem in life in this fatherland is moral and ethics, Education bands represent medium education of child giving an enrichment in moral and ethics in society. Teaching moral value and ethics better more is having the character example of. Do something better then just say of words. that multifarious Value Moral kinds of, including loyalitas, benefaction, honorary, truth, respek, sociability, integrity, justice, cooperation.